Antibacterial polycarbonate film and preparation process thereof

By using a combination of isosorbate polycarbonate and sol-type antibacterial agents in the polycarbonate film, the problem of insufficient antibacterial performance of traditional polycarbonate films is solved, and film preparation with high transparency, good mechanical properties and long-term antibacterial function is achieved.

CN119286226BActive Publication Date: 2025-05-02KUNSHAN DOBESTY OPTOELECTRONIC MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411625097.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-05-02
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Traditional polycarbonate films have shortcomings in antibacterial properties, which are prone to breeding bacteria and leading to food spoilage or cross-infection.

Method used

The combination of isosorbate polycarbonate and crosslinking agent, sol-type antibacterial agent, antioxidant, and leveling agent was used to synthesize alkylated chitosan by the Schiff base method, and react with 3-chloro-2-hydroxypropyltriethylammonium chloride. After preparing the chitosan-type antibacterial agent, TiO2 sol treatment was carried out to form a sol-type antibacterial agent.

Benefits of technology

The prepared antibacterial polycarbonate film has high transparency, good mechanical properties and excellent sterilization function, and can maintain good antibacterial properties in high temperature and humid environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the field of polycarbonate films, and specifically to an antibacterial polycarbonate film and a preparation process thereof. The present application discloses an antibacterial polycarbonate film, which comprises the following raw materials in parts by weight: 100-150 parts of isosorbide-based polycarbonate, 5-8 parts of a cross-linking agent, 10-15 parts of a sol-type antibacterial agent, 1-3 parts of an antioxidant, and 2-4 parts of a leveling agent; the chitosan-type antibacterial agent is treated with TiO2 sol to obtain a sol-type antibacterial agent. The antibacterial polycarbonate film prepared by the present application has high transparency, good mechanical properties and excellent sterilization function through the joint action of isosorbide-based polycarbonate, a cross-linking agent, a sol-type antibacterial agent, an antioxidant, and a leveling agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polycarbonate films, in particular to an antibacterial polycarbonate film and a preparation process thereof. Background Art

[0002] As an important polymer material, polycarbonate film has been widely used in packaging materials, electronic appliances, medical equipment, construction, etc. due to its excellent transparency, good mechanical properties, thermal stability and electrical insulation. Especially in the field of food packaging, polycarbonate film has been widely favored due to its odorless, non-toxic and environmentally friendly properties.

[0003] However, in the actual application of polycarbonate film, especially when it is in direct contact with food or used for medical purposes, its antibacterial property has become an important consideration. Although traditional polycarbonate film has good physical and chemical properties, it has obvious deficiencies in antibacterial properties and is prone to breeding bacteria, leading to problems such as food spoilage or cross infection.

[0004] In order to solve this technical problem, the current technical route mainly focuses on improving the antibacterial properties of polycarbonate films by adding antibacterial agents. These antibacterial agents usually include inorganic antibacterial agents or organic antibacterial agents.

[0005] However, although inorganic antimicrobial agents have significant antimicrobial effects, they often have problems such as easy agglomeration, poor dispersibility, and poor compatibility with substrates, which lead to uneven distribution of antimicrobial agents in polycarbonate films and affect the antimicrobial effect. At the same time, the use of inorganic antimicrobial agents may also affect the transparency and mechanical properties of polycarbonate films.

[0006] Although organic antimicrobial agents have relatively good dispersibility and compatibility, they often have problems such as poor durability of antimicrobial effects and easy decomposition and failure. Especially in harsh environments such as high temperature and humidity, the antimicrobial performance of organic antimicrobial agents will drop significantly or even become completely ineffective.

[0007] Therefore, how to prepare a polycarbonate film that has both good physical and chemical properties and excellent antibacterial properties has become a technical problem that needs to be urgently solved in the current field of materials science. Summary of the invention

[0008] In order to overcome the shortcomings of the prior art, the present invention provides an antibacterial polycarbonate film and a preparation process thereof. The prepared isosorbide-based polycarbonate has better flexibility and processing performance, and at the same time has high transparency, high scratch resistance, excellent thermal stability and low temperature resistance after film formation. The sol-type antibacterial agent treated with TiO2 sol is not easy to agglomerate and has a good bactericidal effect. The prepared antibacterial polycarbonate film has high transparency, good mechanical properties and excellent bactericidal function through the joint action of isosorbide-based polycarbonate, a cross-linking agent, a sol-type antibacterial agent, an antioxidant and a leveling agent.

[0009] The technical solution adopted by the present invention to solve its technical problem is:

[0010] In one aspect, the present application provides an antibacterial polycarbonate film, comprising the following raw materials in parts by weight:

[0011] 100-150 parts of isosorbide-based polycarbonate, 5-8 parts of cross-linking agent, 10-15 parts of sol-type antibacterial agent, 1-3 parts of antioxidant, 2-4 parts of leveling agent;

[0012] The preparation method of the sol-type antibacterial agent comprises the following steps:

[0013] Alkylated chitosan was synthesized by reacting chitosan with n-butyraldehyde via the Schiff base method;

[0014] 3-Chloro-2-hydroxypropyltriethylammonium chloride was synthesized using triethylamine and epichlorohydrin as raw materials;

[0015] The alkylated chitosan and 3-chloro-2-hydroxypropyltriethylammonium chloride are reacted at 55-60° C. for 4-6 hours to prepare a chitosan-based antibacterial agent;

[0016] The chitosan type antibacterial agent is treated with TiO2 sol to obtain a sol type antibacterial agent.

[0017] In one or more technical solutions, the molar ratio of the alkylated chitosan to 3-chloro-2-hydroxypropyltriethylammonium chloride is 1:1.

[0018] In one or more technical solutions, the number average molecular weight of the isosorbide-based polycarbonate is 25,800 g / mol.

[0019] In one or more technical solutions, the method for preparing the isosorbide-based polycarbonate comprises the following steps:

[0020] In a nitrogen environment, diphenyl carbonate, isosorbide, 1,4-cyclohexanedimethanol and a catalyst are added into a reactor; the temperature is raised to 110-120°C and kept warm for 20 minutes; the temperature is continued to be raised and reacted at 170°C for 30 minutes; and then the mixture is subjected to pre-polycondensation and polycondensation treatment to obtain isosorbide-based polycarbonate.

[0021] In one or more technical solutions, the molar ratio of diphenyl carbonate, isosorbide and 1,4-cyclohexanedimethanol is 1.05:0.7:0.3.

[0022] In one or more technical solutions, the catalyst is DPU (N,N′-diphenylurea).

[0023] In one or more technical solutions, the cross-linking agent is citric acid.

[0024] Specifically in this application, a cross-linking agent such as citric acid helps improve the mechanical properties of the film, including tear strength. By promoting cross-linking between molecules, the toughness of the material is increased, making the film less likely to break even under external forces; at the same time, the cross-linking agent can promote the uniform distribution of the antimicrobial agent in the polycarbonate matrix and help form a stable network structure to prevent the migration or loss of the antimicrobial agent, thereby ensuring that the film has a continuous antimicrobial effect throughout its service life.

[0025] In one or more technical solutions, the TiO2 sol is anatase phase nano-TiO2 sol.

[0026] In one or more technical solutions, the leveling agent is LGH-7499 leveling agent. Leveling agents, such as LGH-7499, help to form a smooth and uniform surface during the film manufacturing process by reducing surface defects such as orange peel texture, pinholes, etc.

[0027] In one or more technical solutions, the antioxidant is a hindered phenol antioxidant. Specifically, the antioxidant can inhibit or slow down the aging phenomenon of the polycarbonate material caused by oxidation during processing or use.

[0028] On the other hand, the present application provides a process for preparing an antibacterial polycarbonate film, comprising the following steps:

[0029] (1) Preparation of sol-type antibacterial agent

[0030] Alkylated chitosan was synthesized by reacting chitosan with n-butyraldehyde via the Schiff base method;

[0031] 3-Chloro-2-hydroxypropyltriethylammonium chloride was synthesized using triethylamine and epichlorohydrin as raw materials;

[0032] The alkylated chitosan and 3-chloro-2-hydroxypropyltriethylammonium chloride are reacted at 55-60° C. for 4-6 hours to prepare a chitosan-based antibacterial agent;

[0033] The anatase nano-TiO2 sol and the acetic acid solution are stirred and mixed uniformly to obtain a mixed colloidal solution; under stirring at room temperature, the mixed colloidal solution is added dropwise to the colloidal antibacterial agent, stirred sufficiently, and then filtered, washed, and then vacuum dried at 80°C to obtain the colloidal antibacterial agent;

[0034] (2) Isosorbide-based polycarbonate

[0035] In a nitrogen environment, diphenyl carbonate, isosorbide, 1,4-cyclohexanedimethanol and a catalyst are added to a reactor; the temperature is raised to 110-120°C and kept warm for 20 minutes; the temperature is continued to be raised and reacted at 170°C for 30 minutes; and then the reaction is carried out through pre-polycondensation and polycondensation treatment to obtain isosorbide-based polycarbonate;

[0036] (3) Film formation

[0037] The raw materials are fully mixed according to the weight parts of the raw materials of the antibacterial polycarbonate film, and the antibacterial polycarbonate film is prepared by extrusion casting.

[0038] The beneficial effects of the present invention are:

[0039] The isosorbide-based polycarbonate described in the present application effectively improves the brittleness of conventional polycarbonate by introducing 1,4-cyclohexanedimethanol as a flexible monomer, so that the isosorbide-based polycarbonate has better flexibility and processing performance; at the same time, the prepared isosorbide-based polycarbonate has the characteristics of high transparency, high scratch resistance, excellent thermal stability and low temperature resistance after film formation.

[0040] The sol-type antibacterial agent described in the present application is prepared by coating the sol-type antibacterial agent with TiO2 sol; the sol-type antibacterial agent is not easy to agglomerate and has a good bactericidal effect.

[0041] The antibacterial polycarbonate film described in the present application is prepared by isosorbide-based polycarbonate

[0042] The use of cross-linking agent, sol-type antibacterial agent, antioxidant and leveling agent has good transparency, mechanical properties, antibacterial function and long-lasting antibacterial function. DETAILED DESCRIPTION

[0043] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0044] Preparation Example 1

[0045] The preparation method of chitosan antibacterial agent comprises the following steps:

[0046] A1. Add 300 ml of concentrated hydrochloric acid (mass concentration of 36.5%) to the reactor, weigh an equimolar mass of triethylamine and slowly drop it into the reactor, and react at 30°C for 1 hour; after the reaction is completed, adjust the pH to 8, slowly drop epichlorohydrin (epichlorohydrin: triethylamine = 0.9 mol: 1 mol), and react at a water bath temperature of 35°C for 5 hours;

[0047] Extract twice with carbon tetrachloride, add water and perform rotary evaporation to obtain 3-chloro-2-hydroxypropyltriethylammonium chloride;

[0048] A2. Dissolve 10 g of chitosan in 300 ml of 3% acetic acid solution, stir at room temperature until dissolved, then add 18 ml of n-butyraldehyde, and stir thoroughly at room temperature for 10 hours; then add sodium hydroxide solution to adjust the pH to 4.5, then add 0.1 g of 10% NaBH4 solution, and react at 45°C for 6 hours; after the reaction, adjust the pH of the solution to 8 until precipitation occurs, add 70% ethanol by volume, let stand for precipitation, centrifuge, repeat washing twice, and dry the product to obtain alkylated chitosan;

[0049] A3. Place the alkylated chitosan prepared in step A2, distilled water (the amount of distilled water added is 10 times the weight of NaOH solid), NaOH solid, and 3-chloro-2-hydroxypropyltriethylammonium chloride prepared in step A1 into a reactor, and react at 50° C. for 4 hours; after the reaction, adjust the pH to 8 with hydrochloric acid solution, cool the product to room temperature, add an equal volume of anhydrous ethanol, and let it stand for precipitation;

[0050] After the product is completely precipitated, it is washed with a 60% ethanol solution by volume, centrifuged, and washed repeatedly for 5 times. After the product is dried, a chitosan-based antibacterial agent is obtained. In step A2, the molar ratio of alkylated chitosan, NaOH solid, and 3-chloro-2-hydroxypropyltriethylammonium chloride is 1:4:1.

[0051] Among them, chitosan comes from Sinopharm Chemical Reagent Co., Ltd.

[0052] In the preparation process of the above-mentioned chitosan antibacterial agent, the chemical reaction process involved is:

[0053]

[0054] The prepared chitosan antibacterial agent was analyzed by Fourier transform infrared spectroscopy:

[0055] Results: Chitosan antibacterial agent showed a peak at 1060 cm-1 The CO stretching vibration peak of the primary alcohol near 1150 cm -1 The absorption peak of the nearby dialkyl ether is enhanced, indicating that the quaternary ammonium group on 3-chloro-2-hydroxypropyltriethylammonium chloride is introduced into the chitosan molecule by forming an ether bond with the hydroxyl group on the C-6 of the glucose ring. Therefore, the corresponding groups (alkyl chains and quaternary ammonium groups) are indeed introduced into the chitosan-type antibacterial agent.

[0056] Preparation Example 2

[0057] The preparation of the melt-type antibacterial agent comprises the following steps:

[0058] B1. The anatase nano-TiO2 sol was stirred and mixed evenly with 5 times the volume concentration of 5% acetic acid solution; chitosan antibacterial agent was added at 45°C, and the mixture was stirred at a speed of 200r / min for 2 hours; then filtered, washed, and dried in vacuum at 80°C to obtain a molten antibacterial agent;

[0059] The mass ratio of anatase phase nano-TiO2 sol to chitosan antibacterial agent is 2: 1. Anatase nano-TiO2 sol comes from Hunan Titanium Tang Nanotechnology Co., Ltd.

[0060] Preparation Example 3

[0061] The preparation method of isosorbide-based polycarbonate comprises the following steps:

[0062] C1. The reactor was first replaced with nitrogen three times to exclude oxygen, diphenyl carbonate, isosorbide, and 1,4-cyclohexanedimethanol were added to the reactor, and the mixture was heated to 110°C. After all the raw materials were melted, stirring was started and the catalyst DPU was added, and the mixture was stirred for 15 minutes;

[0063] C2. Set the temperature to 170°C, maintain the pressure at 20 kPa, and carry out the transesterification reaction for 30 minutes;

[0064] C3. When the temperature of phenol rises rapidly, it indicates that the transesterification reaction begins. When the temperature of phenol begins to decrease, the temperature is gradually raised to 220°C to ensure that phenol is removed from the reaction system in time;

[0065] When the temperature of phenol vapor decreases, the temperature is raised to 240°C, the vacuum degree is slowly increased to 100 Pa, and the reaction is continued for 1 hour; when the temperature of phenol decreases to room temperature and the pressure is stable, the reaction is stopped;

[0066] C4. After the system was cooled to room temperature, the product was dissolved in dichloromethane and precipitated in anhydrous methanol to obtain a white solid, which was vacuum dried at 60°C for 24 hours to obtain isosorbide-based polycarbonate.

[0067] Among them, diphenyl carbonate was obtained from Mitsubishi Chemical Corporation.

[0068] The prepared isosorbide-based polycarbonate was tested by Fourier transform infrared spectroscopy, and the results were as follows:

[0069] The stretching vibration absorption peak of the carbonate group C=O is located at about 1750 cm -1 This is the characteristic absorption peak of the carbonate group in the polycarbonate structure, indicating that the carbonate group has been successfully introduced into the copolymer.

[0070] The absorption peak of OCO is located at about 1250 cm -1 This is the characteristic absorption peak of the ether bond connecting the oxygen atom and the carbon atom in the carbonate group, which further confirms the structure of polycarbonate.

[0071] -Characteristic absorption peak of CH2: located at 2979 cm -1 This is the characteristic absorption peak of methyl in polycarbonate.

[0072] Characteristic absorption peak of -CH: located at 2879 cm -1 This is the characteristic absorption peak of methylene in polycarbonate. The existence and position of these absorption peaks are similar to those of polycarbonate homopolymers, indicating that isosorbide-based polycarbonate copolymers were successfully synthesized by introducing 1,4-cyclohexanedimethanol monomers, and the basic structural characteristics of polycarbonate were retained in the isosorbide-based polycarbonate copolymers.

[0073] At the same time, gel permeation chromatography was used to detect the isosorbide-based polycarbonate, and its number average molecular weight (Mn) was 25800 g / mol.

[0074] The chemical reaction equations involved are as follows:

[0075]

[0076] In the following examples and comparative examples, the hindered phenol antioxidant is antioxidant 2246;

[0077] Example 1

[0078] An antibacterial polycarbonate film comprises the following raw materials in parts by weight:

[0079] 100 parts of isosorbide-based polycarbonate (from Preparation Example 3), 5 parts of citric acid, 10 parts of sol-type antibacterial agent (from Preparation Example 2), 1 part of hindered phenol antioxidant, and 2 parts of LGH-7499 leveling agent;

[0080] The method for preparing an antibacterial polycarbonate film comprises the following steps:

[0081] First, according to the precise weight of each raw material required for the antibacterial polycarbonate film, these raw materials are fully mixed; then, the fully mixed raw materials are sent to a twin-screw extruder and made into granules through melt blending technology. Then, on a casting unit, it is extruded and cast into a film, and after a drafting process, an antibacterial polycarbonate film is obtained.

[0082] The process conditions are as follows: the screw speed of the extruder is controlled to 15 rpm, the slit gap of the die is set to 0.55 mm, and the die temperature is maintained at 220°C; the temperature of the casting roll is set to 150°C; at the same time, the draft ratio is set to 35; the pores of the obtained antibacterial polycarbonate film are controlled at 20±0.5 microns.

[0083] Example 2

[0084] An antibacterial polycarbonate film comprises the following raw materials in parts by weight:

[0085] Isosorbide-based polycarbonate (from Preparation Example 3) 130 parts, citric acid 7 parts, sol-type antibacterial agent (from Preparation Example 2) 13 parts, hindered phenol antioxidant 2 parts, LGH-7499 leveling agent 3 parts;

[0086] The remaining conditions are the same as those in Example 1.

[0087] Example 3

[0088] An antibacterial polycarbonate film comprises the following raw materials in parts by weight:

[0089] 150 parts of isosorbide-based polycarbonate (from Preparation Example 3), 8 parts of citric acid, 15 parts of sol-type antibacterial agent (from Preparation Example 2), 3 parts of hindered phenol antioxidant, and 4 parts of LGH-7499 leveling agent;

[0090] The remaining conditions are the same as those in Example 1.

[0091] Example 4

[0092] An antibacterial polycarbonate film comprises the following raw materials in parts by weight:

[0093] Isosorbide-based polycarbonate (from Preparation Example 3) 110 parts, citric acid 6 parts, sol-type antibacterial agent (from Preparation Example 2) 11 parts, hindered phenol antioxidant 1 part, LGH-7499 leveling agent 3 parts;

[0094] The remaining conditions are the same as those in Example 1.

[0095] Example 5

[0096] An antibacterial polycarbonate film comprises the following raw materials in parts by weight:

[0097] 130 parts of diphenyl carbonate (from Preparation Example 3), 7 parts of citric acid, 14 parts of sol-type antibacterial agent (from Preparation Example 2), 2 parts of hindered phenol antioxidant, 3 parts of LGH-7499 leveling agent;

[0098] The remaining conditions are the same as those in Example 1.

[0099] Comparative Example 1

[0100] Polycarbonate film, in parts by weight, comprises the following materials:

[0101] 100 parts of diphenyl carbonate (from Preparation Example 3), 5 parts of citric acid, 10 parts of sol-type antibacterial agent (from Preparation Example 2), 1 part of hindered phenol antioxidant, and 2 parts of LGH-7499 leveling agent;

[0102] The remaining conditions are the same as those in Example 1.

[0103] Comparative Example 2

[0104] Polycarbonate film, in parts by weight, comprises the following materials:

[0105] 100 parts of isosorbide-based polycarbonate (from Preparation Example 3), 10 parts of sol-type antibacterial agent (from Preparation Example 2), 1 part of hindered phenol antioxidant, and 2 parts of LGH-7499 leveling agent;

[0106] The remaining conditions are the same as those in Example 1.

[0107] Comparative Example 3

[0108] Polycarbonate film, in parts by weight, comprises the following materials:

[0109] 100 parts of isosorbide-based polycarbonate (from Preparation Example 3), 5 parts of citric acid, 1 part of hindered phenol antioxidant, and 2 parts of LGH-7499 leveling agent;

[0110] The remaining conditions are the same as those in Example 1.

[0111] Comparative Example 4

[0112] Polycarbonate film, in parts by weight, comprises the following materials:

[0113] 100 parts of isosorbide-based polycarbonate (from Preparation Example 3), 5 parts of citric acid, 10 parts of chitosan-based antibacterial agent (from Preparation Example 1), 1 part of hindered phenol antioxidant, and 2 parts of LGH-7499 leveling agent;

[0114] The remaining conditions are the same as those in Example 1.

[0115] Comparative Example 5

[0116] Polycarbonate film, in parts by weight, comprises the following materials:

[0117] 100 parts of isosorbide-based polycarbonate (from Preparation Example 3), 5 parts of citric acid, 10 parts of anatase-type nano-TiO2 sol (from Preparation Example 2), 1 part of hindered phenol antioxidant, and 2 parts of LGH-7499 leveling agent;

[0118] The remaining conditions are the same as those in Example 1.

[0119] The polycarbonate films prepared in Examples 1-5 and Comparative Examples 1-5 were subjected to the following performance tests, and the test results are summarized in Table 1:

[0120] 1. Light transmittance test

[0121] Tested with a haze meter.

[0122] 2. Antimicrobial testing standards and operating procedures

[0123] ①Antibacterial test standards:

[0124] GB / T 31402-2015 Test method for antibacterial properties of plastic surfaces, JC939 Antibacterial properties of antibacterial plastic pipes for construction, test bacteria: Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 6538.

[0125] ② Antibacterial test steps

[0126] The test was carried out in accordance with the antibacterial plastic testing standard GB / T 31402-2015. The specific steps are as follows: Disinfect the sample to be tested with 75% ethanol and dry it, and dilute the bacteria with sterile water to a bacterial suspension of appropriate concentration for use. Take 0.2m of the bacterial suspension and drop it on the surface of the sample, cover it with a 0.1mm thick polyethylene film (4.0cmx4.0cm) to form a uniform liquid film between the sample and the film. Incubate at 37°C and maintain a relative humidity of 90% for 18 to 24 hours. Wash the bacterial solution with sterile water, dilute it into an appropriate concentration gradient, and take 0.1mL and evenly spread it on the prepared sterile agar medium. Incubate at 37°C for 18 to 24 hours and observe the results. The negative control is replaced by a sterile plate, and other operations are the same; the antibacterial rate is calculated by the JC939-2017 method;

[0127] ③Test of antibacterial durability

[0128] First, irradiate the sample with an 80W UV lamp for 2 hours (at a distance of 10cm), and then place it at room temperature for 5 hours; then test it according to GB / T 31402-2015 standard.

[0129] 3. Tear strength test

[0130] The test was carried out according to the method of standard GB / T 16578.2-2009;

[0131] Table 1

[0132]

[0133] From the results in Table 1, we can see that:

[0134] The films prepared in Examples 1-5 have a light transmittance between 90.6% and 92.9%, showing good transparency; the films prepared in Examples 1-5 have a tear strength between 6.12 N / mm and 6.38 N / mm, showing good mechanical strength. The films prepared in Examples 1-5 have excellent antibacterial properties against Staphylococcus aureus and Escherichia coli at room temperature, with an antibacterial rate of 99.9%. After the antibacterial durability test, the antibacterial rate against the two test strains remained at 99.9%, indicating that the antibacterial properties of the film remain good after ultraviolet irradiation.

[0135] The light transmittance of the film prepared in Comparative Example 1 was 93.5%, which was higher than 90.6% in Example 1. The tear strength was 3.58 N / mm, which was lower than 6.12 N / mm in Example 1. In terms of antibacterial performance, the room temperature and antibacterial durability inhibition rates against Staphylococcus aureus and Escherichia coli were both 99.9%, which was the same as in Example 1.

[0136] Compared with Example 1, the film of Comparative Example 1 has a higher light transmittance because it does not use diphenyl carbonate as a main component, which may make the film more transparent and reduce the tear strength.

[0137] The film properties of Comparative Example 2 are as follows:

[0138] The light transmittance is 81.6%, which is significantly lower than 90.6% of Example 1.

[0139] The tear strength was 4.59 N / mm, which was also lower than that of Example 1 (6.12 N / mm).

[0140] The room temperature antibacterial activity (inhibition rate) against Staphylococcus aureus and Escherichia coli was 99.9%, the same as in Example 1, but the antibacterial durability (inhibition rate) was 78.9% and 65.8%, respectively, significantly lower than 99.9% in Example 1.

[0141] Compared with Example 1, the difference in film performance of Comparative Example 2 is mainly reflected in light transmittance, tear strength and antibacterial durability. No citric acid was added in Comparative Example 2, resulting in a decrease in the mechanical properties of the film, that is, the tear strength is low. In addition, the lack of citric acid also affects the uniformity and density of the film, and then affects the light transmittance. The reason for the reduction in antibacterial durability may be that due to the lack of support from the cross-linking agent, the stability of the antibacterial agent in the film is affected. After the antibacterial durability test (ultraviolet light irradiation treatment), the effectiveness of the antibacterial agent decreases, so the antibacterial rate decreases. By adding an appropriate amount of citric acid, Example 1 not only improves the physical properties of the film, but also enhances the fixation of the antibacterial agent, thereby making the antibacterial effect more lasting.

[0142] The film properties of Comparative Example 3 are as follows:

[0143] The light transmittance is 88.5%, which is lower than 90.6% of Example 1.

[0144] The tear strength is 5.79 N / mm, which is also lower than 6.12 N / mm of Example 1.

[0145] The room temperature antibacterial activity (inhibition rate) against Staphylococcus aureus is 38.9%, and that against Escherichia coli is 25.7%, which are much lower than 99.9% in Example 1.

[0146] In terms of antibacterial durability (inhibition rate), the rate against Staphylococcus aureus was 33.6%, and the rate against Escherichia coli was 18.7%, which were also much lower than 99.9% in Example 1.

[0147] The main difference between Comparative Example 3 and Example 1 is that no sol-type antibacterial agent is added. Example 1 adds a specific sol-type antibacterial agent (chitosan antibacterial agent obtained by TiO2 sol treatment) to give the film good antibacterial properties. In Comparative Example 3, due to the lack of sol-type antibacterial agent, the antibacterial properties of the film are significantly reduced. In addition, the presence of sol-type antibacterial agent not only helps to improve the antibacterial effect, but also has a certain positive effect on the light transmittance and mechanical properties of the film. Therefore, the film of Comparative Example 3 without adding antibacterial agent performs poorly in terms of antibacterial properties, and is also inferior to Example 1 in terms of light transmittance and tear strength.

[0148] The film properties of Comparative Example 4 are as follows:

[0149] The light transmittance is 88.1%, which is lower than 90.6% of Example 1.

[0150] The tear strength was 5.91 N / mm, which was lower than that of Example 1 (6.12 N / mm).

[0151] In terms of room temperature antibacterial activity, the antibacterial rate against Staphylococcus aureus was 98.9%, and the antibacterial rate against Escherichia coli was 86.3%, which were lower than 99.9% in Example 1.

[0152] In terms of antibacterial durability, the antibacterial rate against Staphylococcus aureus was 34.7%, and the antibacterial rate against Escherichia coli was 20.5%, which were also much lower than 99.9% in Example 1.

[0153] Compared with Example 1, the film performance of Comparative Example 4 is relatively poor, mainly because Comparative Example 4 uses a chitosan antibacterial agent instead of a sol-type antibacterial agent. Although the chitosan antibacterial agent has a certain antibacterial effect, due to the lack of coating treatment of TiO2 sol, its anti-ultraviolet ability is relatively poor. The sol-type antibacterial agent used in Example 1 is treated with TiO2 sol, which can not only prevent the TiO2 sol from agglomerating, but also improve the anti-ultraviolet effect and bactericidal effect of the chitosan antibacterial agent. Therefore, the film of Example 1 performs better in antibacterial performance, especially in the durability test after ultraviolet irradiation, it can still maintain a high antibacterial rate. In addition, the sol-type antibacterial agent may also have a positive effect on the transparency and mechanical properties of the film, so that the film of Example 1 is superior to Comparative Example 4 in both light transmittance and tear strength.

[0154] The film properties of Comparative Example 5 are as follows:

[0155] The light transmittance is 87.7%, which is lower than 90.6% of Example 1.

[0156] The tear strength was 6.05 N / mm, slightly lower than that of Example 1 (6.12 N / mm).

[0157] In terms of room temperature antibacterial activity, the inhibition rate against Staphylococcus aureus was 47.6%, and the inhibition rate against Escherichia coli was 37.2%, which were much lower than 99.9% in Example 1.

[0158] In terms of antibacterial durability, the inhibition rate against Staphylococcus aureus was 46.6%, and the inhibition rate against Escherichia coli was 36.3%, which were also much lower than 99.9% in Example 1.

[0159] Compared with Example 1, the main difference between Comparative Example 5 and Example 1 is that different antibacterial agents are used. The antibacterial agent used in Example 1 is a sol-type antibacterial agent obtained by treating a chitosan antibacterial agent and a TiO2 sol, while Comparative Example 5 uses anatase nano-TiO2 sol. Although both contain TiO2, the chitosan antibacterial agent has better dispersibility and stability after being treated with TiO2 sol, can more effectively resist bacteria, and is not easy to agglomerate, and has a significant antibacterial effect. However, when TiO2 sol is applied to a film, the antibacterial effect is not ideal;

[0160] Therefore, the film of Example 1 has better antibacterial performance. In addition, chitosan itself has certain biological activity, and the synergistic effect with TiO2 sol can improve the durability of the antibacterial effect of the film.

[0161] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. An antibacterial polycarbonate film, characterized in that: In parts by weight, it includes the following raw materials: 100-150 parts of isosorbide-based polycarbonate, 5-8 parts of cross-linking agent, 10-15 parts of sol-type antibacterial agent, 1-3 parts of antioxidant, 2-4 parts of leveling agent; The cross-linking agent is citric acid; The preparation method of the sol-type antibacterial agent comprises the following steps: Alkylated chitosan was synthesized by reacting chitosan with n-butyraldehyde via the Schiff base method; The alkylated chitosan and 3-chloro-2-hydroxypropyltriethylammonium chloride are reacted at 55-60° C. for 4-6 hours to prepare a chitosan-based antibacterial agent; The chitosan type antibacterial agent is treated with TiO2 sol to obtain a sol type antibacterial agent; The preparation method of the isosorbide-based polycarbonate comprises the following steps: In a nitrogen environment, diphenyl carbonate, isosorbide, 1,4-cyclohexanedimethanol and a catalyst are added to a reactor; the temperature is raised to 110-120°C and kept warm for 20 minutes; the temperature is continued to be raised and reacted at 170°C for 30 minutes; and then the reaction is carried out through pre-polycondensation and polycondensation treatment to obtain isosorbide-based polycarbonate; The feeding molar ratio of diphenyl carbonate, isosorbide and 1,4-cyclohexanedimethanol is 1.05:0.7:0.

3.

2. The antibacterial polycarbonate film according to claim 1, characterized in that: The molar ratio of the alkylated chitosan to 3-chloro-2-hydroxypropyltriethylammonium chloride is 1:

1.

3. The antibacterial polycarbonate film according to claim 1, characterized in that: The number average molecular weight of the isosorbide-based polycarbonate is 25800 g / mol.

4. The antibacterial polycarbonate film according to claim 1, characterized in that: The catalyst is DPU.

5. The antibacterial polycarbonate film according to claim 1, characterized in that: The TiO2 sol is anatase phase nano-TiO2 sol.

6. The antibacterial polycarbonate film according to claim 1, characterized in that: The antioxidant is a hindered phenol antioxidant.

7. A process for preparing an antibacterial polycarbonate film according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Preparation of sol-type antibacterial agent Alkylated chitosan was synthesized by reacting chitosan with n-butyraldehyde via the Schiff base method; The alkylated chitosan and 3-chloro-2-hydroxypropyltriethylammonium chloride are reacted at 55-60° C. for 4-6 hours to prepare a chitosan-based antibacterial agent; The anatase nano-TiO2 sol and the acetic acid solution are stirred and mixed uniformly to obtain a mixed colloidal solution; under stirring at room temperature, the mixed colloidal solution is added dropwise to the chitosan type antibacterial agent, stirred sufficiently, and then filtered, washed, and then vacuum dried at 80°C to obtain a sol-type antibacterial agent; (2) Isosorbide-based polycarbonate In a nitrogen environment, diphenyl carbonate, isosorbide, 1,4-cyclohexanedimethanol and a catalyst are added to a reactor; the temperature is raised to 110-120°C and kept warm for 20 minutes; the temperature is continued to be raised and reacted at 170°C for 30 minutes; and then the reaction is carried out through pre-polycondensation and polycondensation treatment to obtain isosorbide-based polycarbonate; (3) Film formation According to the weight composition of the antibacterial polycarbonate film, various raw materials are fully mixed, and the antibacterial polycarbonate film is prepared by extrusion casting.

Citation Information

Patent Citations

  • Titanium dioxide reinforced montmorillonite modified polycarbonate plastic and preparation method thereof

    CN109021532A

  • Antibacterial polycarbonate plastic and preparation method thereof

    CN111454560A